Measuring and improving testability of system requirements in an industrial context by applying the goal question metric approach - Beer, Armin; Felderer, Michael (2018 IEEE ACM 5th International Workshop on Requirements Engineering and Testing (RET), 2018)
Testing is subject to two basic constraints, namely cost and quality. The cost depends on the efficiency of the testing activities as well as their quality and testability. The author's practical experience in large-scale systems shows that if the requirements are adapted iteratively or the architecture is altered, testability decreases. However, what is often lacking is a root cause analysis of the testability degradations and the introduction of improvement measures during software development. In order to introduce agile practices in the rigid strategy of the V-model, good testability of software artifacts is vital. So testability is also the bridgehead towards agility. In this paper, we report on a case study in which we measure and improve testability on the basis of the Goal Question Metric Approach.